Work in Progress: Improving Learning Performance using Programming Methodology - Almeida, Maria Emilia Bigotte de (2019)
The program “Introduction to programming in the first cycle of basic education” initiated in 2015 has provided the opportunity to develop computational thinking and digital literacy among students. The existing literature suggests that Scratch programming language may have a strong influence on the skills acquired by students in classroom. In this context, it is intended to build an intervention with objectives that fit into the Student Profile leaving compulsory education and developed within the scope of curricular flexibility, recommended for the 1st year of basic education. The applied methodology aims to evaluate the impact on students' knowledge (mathematics and mother tongue), attitudes (in relation to knowledge and citizenship) and on the capacities (cognitive, emotional and practical) as well as in the school community (students, teachers and families).